RELIGIOUS HARMONY EDUCATION SYSTEM IN EKASARI VILLAGE, JEMBRANA DISTRICT: Overview of Sociology of Religious Education - Ni Kadek Ayu Kristini Putri; I Gusti Ngurah Sudiana; I Nyoman Yoga Segara (Institut Hindu Dharma Negeri Denpasar, 2021)
Religious harmony in Indonesia and Bali was still a severe problem marked by the high potential for social conflicts with religious backgrounds. However, the people of Ekasari Village could maintain religious harmony in their area from generation to generation while at the same time providing space for every religious community to articulate their religious identity without pressure from other people. Religious harmony in Ekasari Village showed a strong relationship between education, social values, and religion. This study was conducted to analyze the education system for religious harmony in Ekasari Village from a sociological review of religious education based on the theory of structural functionalism, constructivism, and social action. The research was carried out by applying qualitative methods through observation, in-depth interviews, and document studies. The data were analyzed descriptivelyinterpretatively through three stages, namely data reduction, data presentation, and verification. This study found that the education system for religious harmony in Ekasari Village takes place in the realm of family, school, community, religious institutions, state, and civil society, as well as the mass media. This education system holistically encourages the internalization of knowledge, attitudes, and harmonious behaviour within religious communities.